Redesain Dimensi Tiang Pancang Baja di Dermaga 02 Terminal Petikemas Pelabuhan Patimban - Gunanta, Ezra Valentino; Dwisa, Cokorda Bagus Purnama; Heryanto, Benny (Fakultas Teknik Transportasi dan Logistik Trisakti, 2024)
The port is located in Patimban, Subang district, West Java. One of the facilities in the port of Patimban is berth of the container terminal 02. The port has a length and width of 451 x 32 meters and has a steel pipe pile diameter of 1300 mm with a thickness of 19 mm that can serve ships with a size of 143.000 DWT. This final task aims to redesign the dimensions of the steel pipe pile to a diameter of 1100 mm and to find out whether the structure of the bridge that has been changed after its diameter is still strong to withstand the existing load. On this final task to find out the strength of the bridge structure using the help of the software SAP2000 and the capacity calculation of the steel pile will use the method of calculating the foundation in accordance with mayerhoff. The calculation of the base of the pile from the axial style of a pile, the lateral style, the X and Y slide survey, the two-way slide review showed the result that the berth that had been changed its dimensions to 1100 mm was still strong to withstand the existing load.